Moss 0.2: melhorias na interface e novas funcionalidades para um simulador de sistema operacional - Costa, Antonio Victor Teixeira da (Universidade Federal Rural do Semi-Árido, 2019)
This article describes the changes made to the MOSS interface and the implementation of new features for process, memory and file managers, bringing more information about what is being simulated by the operating system and allowing a better understanding of its operation for students. This new version was called MOSS 0.2, which is presented in detail.
Artigo Acadêmico
Keywords: SO; Simulador; Mars; Moss; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO